2013
DOI: 10.1097/mco.0000000000000013
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein is beneficial to bone health under conditions of adequate calcium intake

Abstract: Purpose of review To underscore recent clinical studies, which evaluate the association between dietary protein and bone health. Recent findings Epidemiologic studies show greater protein intake to be beneficial to bone health in adults. In addition, randomized controlled trials show that protein's positive effect on bone health is augmented by increased calcium intake. The relation between dietary protein and fracture risk is unclear. Dietary protein may positively impact bone health by increasing muscle ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 26 publications
2
49
0
2
Order By: Relevance
“…Evidence-based analysis using the application of Hill's criteria for causality showed clearly that "A causal association between dietary acid load and osteoporotic bone disease is not supported by evidence…" (Fenton et al, 2011). It has in fact been suggested that dietary protein is a nutrient that is supportive of bone health, but this is only the case when calcium intakes are adequate (Mangano et al 2014). Thus, we propose, as reviewed in several recent publications recommending greater protein intakes (≥1.2 g/(kg·day)) for older persons (Bauer et al 2013;Deutz et al 2014), that there is no evidence supportive of higher protein intakes leading to renal failure and/or poor bone health.…”
Section: Health Impactsmentioning
confidence: 99%
“…Evidence-based analysis using the application of Hill's criteria for causality showed clearly that "A causal association between dietary acid load and osteoporotic bone disease is not supported by evidence…" (Fenton et al, 2011). It has in fact been suggested that dietary protein is a nutrient that is supportive of bone health, but this is only the case when calcium intakes are adequate (Mangano et al 2014). Thus, we propose, as reviewed in several recent publications recommending greater protein intakes (≥1.2 g/(kg·day)) for older persons (Bauer et al 2013;Deutz et al 2014), that there is no evidence supportive of higher protein intakes leading to renal failure and/or poor bone health.…”
Section: Health Impactsmentioning
confidence: 99%
“…Although in the past high protein intake was often assumed to exert a primarily detrimental impact on bone mass and skeletal health, the majority of studies indicate the opposite. A low-protein diet is associated with a higher risk of hip fractures, however, only under conditions of adequate Ca intake (83,84) .…”
Section: Discussionmentioning
confidence: 99%
“…Specific mechanisms may include increased intestinal absorption of calcium, increased IGF-1 release (a main signal for bone health), parathyroid hormone inhibition, and increased muscle strength supporting the underlying skeleton. This protective effect of protein on bone is, however, thought to exist only in the setting of adequate calcium intake [58].…”
Section: Recommended Dietary Allowancementioning
confidence: 99%
“…The practice of ingesting purified protein among strength athletes is thought to be a reflection of the concern that traditional high-protein diets may be atherogenic (as a result of relying heavily on meats) [51]. However, while increased protein intake does increase calciuria, other compensatory mechanisms yield an increase in bone mineral density [58]. Specific mechanisms may include increased intestinal absorption of calcium, increased IGF-1 release (a main signal for bone health), parathyroid hormone inhibition, and increased muscle strength supporting the underlying skeleton.…”
Section: Recommended Dietary Allowancementioning
confidence: 99%